1998
DOI: 10.1136/vr.143.5.136
|View full text |Cite
|
Sign up to set email alerts
|

Serological and immunohistochemical study of African swine fever in wild boar in Spain

Abstract: A serological and immunohistochemical study of African swine fever was carried out in wild boar killed in seven municipalities in the north of the province of Córdoba during two hunting seasons (1991-92 and 1992-93), when the area was affected by the disease. Fourteen of 147 wild boar analysed by ELISA and immunoblotting had antibodies to African swine fever virus. The immunohistochemical study revealed that four cases (two seropositive and two seronegative) showed immunoreactivity to the anti-VP73 monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 8 publications
2
39
0
Order By: Relevance
“…This species is highly susceptible to both natural and experimental infection (McVicar et al, 1981); in the Iberian Peninsula, it perished in large numbers following initial introduction of ASFV (Wilkinson, 1989). Depending on the virulence of circulating strains, some animals survive, and positive animals have been detected during serological surveys (Perez et al 1998). In Florida, it was observed that feral pigs were extremely susceptible to domestic pig isolates from the Dominican Republic (McVicar et al, 1981).…”
Section: Role Of Sus Scrofa In the Epidemiology Of Asfmentioning
confidence: 99%
See 3 more Smart Citations
“…This species is highly susceptible to both natural and experimental infection (McVicar et al, 1981); in the Iberian Peninsula, it perished in large numbers following initial introduction of ASFV (Wilkinson, 1989). Depending on the virulence of circulating strains, some animals survive, and positive animals have been detected during serological surveys (Perez et al 1998). In Florida, it was observed that feral pigs were extremely susceptible to domestic pig isolates from the Dominican Republic (McVicar et al, 1981).…”
Section: Role Of Sus Scrofa In the Epidemiology Of Asfmentioning
confidence: 99%
“…However, several years later, the number of seropositive animals increased to 10% in some areas and seropositivity levels coincided with areas where domestic pigs remained infected (Perez et al, 1998), suggesting that the initial virulent virus had become attenuated. This again highlights the importance of virus heterogeneity, as ASF virus expression in wild boar populations may change over time and will, together with other factors, be influenced by the virulence of circulating strains.…”
Section: Role Of Sus Scrofa In the Epidemiology Of Asfmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of ASFV infection in wild boar was reported from the Iberian Peninsula (Wilkinson 1984;Arias & Sanchez-Vizcaino 2002), Sardinia (McVicar et al 1981;Laddomada et al 1994;Mannelli et al 1997) and most recently in Russia (OIE WAHID 2009). In areas where domestic pigs were free of the disease, very low prevalence or absence of seropositive wild boars was reported (Perez et al 1998) suggesting limited persistence of the virus in wild boar populations without contact with infected domestic pigs (Laddomada et al 1994;Perez et al 1998;Ruiz-Fons et al 2008). Given the recent development in the Caucasus region and the current situation in Sardinia further research is needed to elucidate the competence of wild boar to act as infection reservoir, and needs to consider potential differences in virulence of ASFV strains.…”
Section: Epidemiology Of African Swine Fevermentioning
confidence: 99%